(untitled) (Revista Contexto & Educação, 2026)
This is a preliminary study aimed at identifying trends in Health Education (HE) in Natural Sciences and Technology textbooks in Brazil. To this end, we considered two approaches to HE: the traditional approach and the pedagogical-reflexive approach. The traditional approach is based on the transmission of health information with the purpose of promoting behavioral change. The pedagogical-reflexive approach, in turn, seeks to construct knowledge for autonomous action, grounded in students’ participation in situations of choice, reflection, and decision-making. The objective of this work is to identify the predominant HE trends in the activities of one of the textbook collections approved in Brazil by the National Textbook and Teaching Materials Program (PNLD/2021). This is a qualitative documentary research. For data collection, we selected one textbook volume from collections intended for High School. The choice of this material was motivated by the presence of a section addressing health-related topics, as well as its current use in public schools in the state of Paraná. The analysis was conducted based on the principles of Content Analysis. The results indicate a predominance of traditional approaches, which do not fully encompass current understandings of HE. It is concluded that the approach adopted in the analyzed textbook contributes to the development of limited conceptions of the health process among students. Considering that textbooks are widely used by teachers to address health-related topics, it is necessary to propose materials aligned with contemporary HE objectives, as well as continuous and rigorous evaluation of such resources.